MENINGKATKAN KESADARAN IBU HAMIL AKAN PEMERIKSAAN ANC MELALUI EDUKASI INOVATIF BERBASIS LEMBAR BALIK - Krisna, Putri; Ariescha, Putri Ayu Yessy; Fitriani, Fitriani; Sari, Ria Novita; Chaniago, Arnia; Purba, Silvia Kartika (INSTITUT KESEHATAN DELI HUSADA, 2025)
The coverage of Antenatal Care (ANC) visits in Indonesia has not yet reached the national target of 95%. Low awareness among pregnant women regarding the importance of ANC remains a challenge, influenced by factors such as education level, knowledge, family support, and limited access to health information. To address this issue, appropriate and effective educational approaches are needed to increase pregnant women's understanding and adherence to routine ANC visits. One effective educational tool is the flip chart, a visual aid composed of sequential pages containing concise and structured health information, supported by illustrations and diagrams. Flip charts promote two-way communication between healthcare providers and clients, delivering information in a gradual and visually engaging manner. This Community Service Program (PKM) aims to raise pregnant women’s awareness and understanding of ANC through flip chart-based education. The flip chart serves not only as an information medium but also as an interactive tool to support informed health decisions. It is expected that this intervention will enhance knowledge and positively influence pregnant women’s behavior in complying with ANC schedules, ultimately contributing to better maternal and fetal health outcomes.